APPLYING ARTIFICIAL INTELLIGENCE TECHNOLOGIES IN INSTALLED VIDEO SURVEILLANCE SYSTEMS TO ENSURE THE SECURITY OF APARTMENTS (International journal of artificial intelligence, 2026)
This scientific article examines the integration of artificial intelligence (AI) technologies into residential security systems to prevent apartment burglaries. Special attention is given to intelligent video surveillance systems installed in the entrances of multi-apartment buildings that can recognize residents, their relatives, and authorized trusted persons. The paper analyzes machine learning methods, computer vision, and biometric identification, as well as the advantages and limitations of their practical application. It is shown that the use of AI can significantly increase the level of security and enable a transition from passive monitoring to active crime prevention. The article also considers the problem of safeguarding residential premises under conditions of increasing burglary rates, discusses the constraints of traditional security systems, and substantiates the expediency of introducing AI into protection solutions. It is demonstrated that AI improves the effectiveness of preventing unlawful actions through intelligent data analysis and threat forecasting. Key implementation directions, as well as challenges and prospects for applying AI in everyday (household) security, are discussed.